Are Social Norms Universal? - Castillo, Geoffrey; Choo, Lawrence; Grimm, Veronika (2019)

Do students behave like real taxpayers in the lab? Evidence from a real effort tax compliance experiment - Choo, Lawrence; Fonseca, Miguel A.; Myles, Gareth D. (Journal of Economic Behavior & Organization, 2016)
We report on data from a real-effort tax compliance experiment using three subject pools: students, who do not pay income tax; company employees, whose income is reported by their employer; and self-employed taxpayers, who are responsible for filing and payment. While compliance behavior is unaffected by changes in the level of, or information about the audit probability, higher fines increase compliance. We find subject pool differences: self-assessed taxpayers are the most compliant, while students are the least compliant. Through a simple framing manipulation, we show that such differences are driven by norms of compliance from outside the lab
Keywords: Tax compliance; Real effort; Field experiment

Information Aggregation in Arrow-Debreu Markets: An Experiment - Choo, Lawrence; Kaplan, Todd R.; Zultan, Ro'i (Experimental Economics, 2017)
Studies of experimental and betting markets have shown that markets are able to efficiently aggregate information dispersed over many traders. We study information aggregation in Arrow-Debreu markets using a novel information structure. Compared to previous studies, the information structure is more complex, allows for heterogeneity in information among traders – which provides insights into the way in which information is gradually disseminated in the market – and generates situations in which all traders hold identical beliefs over the traded assets' values, thus providing a harsh stress test for belief updating. We find little evidence for information aggregation and dissemination in early rounds. Nonetheless, after traders gain experience with the market mechanism and structure, prices converge to reveal the true state of the world. Elicited post-market beliefs reveal that markets are able to efficiently aggregate dispersed information even if individual traders remain uninformed, consistent with the marginal trader hypothesis.
Keywords: Information aggregation; Prediction markets; Arrow-Debreu markets; Red hat puzzle

Remuneration Structure and Whistleblowing Behaviour: An Experimental Investigation - Choo, Lawrence; Grimm, Veronika; Horvath, Gergely; Nitta, Kohei (2016)

Whistleblowing and diffusion of responsibility: An experiment - Choo, Lawrence; Grimm, Veronika; Horváth, Gergely; Nitta, K. (European Economic Review, 2019)
In this paper we examine diffusion of responsibility in a whistleblowing experiment. We use a multi-player asymmetric information ultimatum game where only the proposer and a subset of the responders (the information insiders) know the size of a pot that the proposer distributes among information insiders and outsiders. Insiders have a clear monetary incentive to whistleblow in case of a small pot in order to avoid rejection of seemingly unfair offers by outsiders; in case of a large pot only altruistic motives could explain that insiders whistleblow. We vary the number of information insiders, one or two, who can whistleblow. We find that in all treatments close to 60% of the insiders whistleblow when they are pivotal for both small and large pots. In a treatment where other insider can also blow the whistle, we observe a significant drop in case only altruistic motives can explain whistleblowing. We show that the effect is due to the extensive margin, i.e. the share of whistleblowers drops to 20%, while patterns of active whistleblowers do not change. In case of low pot sizes, where whistleblowing is in line with selfish motives, we do not observe diffusion of responsibility, in spite of a possible free riding incentive due to a positive cost of whistleblowing.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Diffusion of responsibility; Pro-social behaviours; Whistleblowing